Age-related cerebral changes during different n-back tasks: a functional near-infrared spectroscopy study - Zhu, Shizhe; Wang, Qinglei; Kan, Chaojie; Geng, Ayan; Sui, Youxin; Zhuang, Ren; Zhu, Yi; Wang, Tong; Zhu, Lan; Guo, Chuan (Frontiers in Aging Neuroscience, 2024)
The n-back task, a classic paradigm for assessing working memory, is currently widely applied to examine age-related cognitive decline. Not only do peripheral performance differences emerge when compared with young individuals emerge, but central performance, as measured using positron emission tomography and functional magnetic resonance imaging, also shows varying degrees of disparity. However, research utilizing functional near-infrared spectroscopy (fNIRS) in this context remains limited. Therefore, we conducted signal collection using fNIRS data from 18 elderly and 19 young individuals performing different n-back tasks. Our results revealed significant differences in brain activation patterns between the groups. Notably, under the 3-back condition, the older group exhibited reduced activation in irrelevant brain regions adjacent to prefrontal cognitive areas compared with the younger group. Additionally, the older group's performance plateaued at the 2-back level, accompanied by a decline in prefrontal activation. This finding may provide a new target for screening cognitive decline in the future.